Design and evaluation of icephobic coatings for efficient thermal de-icing - Brierley, Jack (2025)
Ice accretion on engineering structures is a significant safety concern, and the current in-use mitigation strategy of electro-thermal de-icing systems is energy-intensive. Icephobic coatings have been identified as a potential zero-energy solution, passively de-icing the surface or altering the accretion formation. Numerous approaches are being studied, and progress is being made towards this goal. However, coating durability remains a significant hurdle.